Urinary levels of the acrolein conjugates of carnosine are associated with inhaled toxicants. (5th December 2020) - O'Toole, Timothy E.; Li, Xiaohong; Riggs, Daniel W.; Hoetker, David J.; Yeager, Ray; Lorkiewicz, Pawel; Baba, Shahid P.; Cooper, Nigel G. F.; Bhatnagar, Aruni
Abstract: Objective: The inhalation of air-borne toxicants is associated with adverse health outcomes which can be somewhat mitigated by enhancing endogenous anti-oxidant capacity. Carnosine is a naturally occurring dipeptide (β-alanine-L-histidine), present in high abundance in skeletal and cardiac muscle. This multi-functional dipeptide has anti-oxidant properties, can buffer intracellular pH, chelate metals, and sequester aldehydes such as acrolein. Due to these chemical properties, carnosine may be protective against inhaled pollutants which can contain metals and aldehydes and can stimulate the generation of electrophiles in exposed tissues. Thus, assessment of carnosine levels, or levels of its acrolein conjugates (carnosine-propanal and carnosine-propanol) may inform on level of exposure and risk assessment. Methods: We used established mass spectroscopy methods to measure levels of urinary carnosine ( n = 605) and its conjugates with acrolein ( n = 561) in a subset of participants in the Louisville Healthy Heart Study (mean age = 51 ± 10; 52% male). We then determined associations between these measures and air pollution exposure and smoking behavior using statistical modeling approaches. Results: We found that higher levels of non-conjugated carnosine, carnosine-propanal, and carnosine-propanol were significantly associated with males ( p < 0.02) and those of Caucasian ethnicity ( p < 0.02). Levels of carnosine-propanol were significantly higher in never-smokers ( p = 0.001) but lower in current smokers ( p = 0.037). This conjugate also demonstrated a negative association with mean-daily particulate air pollution (PM2.5 ) levels ( p = 0.01). Conclusions: These findings suggest that urinary levels of carnosine-propanol may inform as to risk from inhaled pollutants.